Efektivitas Peer Group terhadap Konsumsi Tablet Fe pada Remaja Putri - Esti Nur Rahayu; Nina Mardiana; Lidia Lushinta (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
The problem encountered was the attitude of not wanting to take Fe tablets with the reason that it was uncomfortable because of the bad smell and taste like iron. The factor of routine consumption of Fe tablets can be encouraged by applying the Peer Group Education method. The purpose of this study was to determine the effectiveness of the Peer Group on increasing the consumption of Fe tablets in adolescent girls. Peer groups is a form of education that emphasizes behavior change and this method interaction occurs within the group. This type of research is a Quasi Experiment with a Non Equivalent Control Group Design. The population in this study were all female students of class VIII at SMP Negeri 4 Samarinda, totaling 190 students. Sampling using the Simple Random Sampling technique with the Mann Whittney U-Test test. 85.7% of respondents were in the effective category, and 100% of the respondents were in the routine category. So that there is the effectiveness of the Peer Group on increasing consumption of Fe tablets (p value = 0.00) with a value of = 0.05. Group education by peers (peer education) is a process of communication, information, and education (IEC) carried out by and for peers through the formation of peer groups. It also functions as a forum for sharing among group members so that teenagers exchange ideas and remind each other about consuming Fe tablets.